Civic Engagement in Emerging Adulthood: Variation by Gender and SES, and Association with Personal Adjustment - Laura Sánchez-García; Marta Díez; Inmaculada Sánchez-Queija; Izarne Lizaso; Águeda Parra (SAGE Open)
This study analyzes civic engagement among Spanish emerging adults, exploring its association with psychological well-being and distress, attending to gender differences and other sociodemographic variables. 1,700 university students (64.7% women) aged between 18 and 29 years completed a self-administered questionnaire. Emerging adult women scored higher for civic engagement (civic awareness, civic and electoral participation) than men. Civic awareness correlated positively with flourishing and negatively with distress, especially among women. However, contradictory results were found for civic participation, which correlated positively with flourishing among men, but also correlated positively with distress, especially among women. Our findings help identify the most common dimensions of civic engagement in this vital stage and highlight the important role played by gender in the civic engagement of Spanish emerging adults.